A amplitude da imunidade dos templos religiosos: exoneração de impostos diretos e indiretos - Lima, Daniel Araújo (2006)
In this present research we have the objective of analyzing the extent of the religious temples immunity. Our study will aboard the general situation to appoint when the immunity must be considered or not, regarding, in the first view, the religious activity itself. We will see the incidence of direct taxes (on services, property, income tax etc.) and the indirect taxes (on circulation of goods, on services, on energy etc.). Infra constitutional arguments cannot be used to stop the immunity of Constitution. On the other hand, it is not possible recognize the immunity in all opportunities, even against other principles of Constitution. It is a fact that in this research we used the mainspring of constitutional hermeneutics, the best and modern doctrine about the subject and the more recent precedents of jurisprudence.